Industrial development in a backward region : dynamics of policy - Patnaik, S. C. (New Delhi : Ashish Pub. House, 1988)
Study covers Orissa State, India.
Includes index.
mizan
Keywords: Industrial policy -- India -- Odisha; Industries -- India -- Odisha